방사선과 재학생의 수시출입자 방사선 피폭선량에 대한 고찰 - 박훈희(Hoon-Hee Park) (방사선기술과학, 2018)
The Nuclear Safety Commission amended the Nuclear Safety Act by strengthening the safety management system for the frequent workers to the level of radiation workers. And students entering radiation management zones for testing and practical purposes are subject to frequent workers. It is inevitable that this will incur additional costs. In this paper, the validity of the amendment to the Nuclear Safety Act was to be assessed in terms of radiation protection. Study subjects are from 2014 to 2016, among university students in Seong-nam Korea and comparisons for analyses were made taking into account variables that are differences in annual, practical types, on-class and clinical practice students exposure dose. The analysis showed that exposures between on-class and clinical practice received were less than the annual dose limit of 1 mSv for the public. Then, some alternatives that excluding from frequent workers during on-class practice or mitigating the frequent workers' safety regulation for only on-class frequent workers can be considered. Optimization is how rational is the reduction in exposure dose to the costs required. Therefore, the results are hardly considered for optimization. If the data accumulated, it could be considered that the revision of the act could be evaluated and improved.